Preparation and anti-cancer evaluation of promiximab-MMAE, an anti-CD56 antibody drug conjugate, in small cell lung cancer cell line xenograft models. (26th November 2018) - Yu, Lin; Yao, Yuqin; Wang, Yuxi; Zhou, Shijie; Lai, Qinhuai; Lu, Ying; Liu, Yu; Zhang, Ruirui; Wang, Ruixue; Liu, Chuang; Gou, Lantu; Chen, Xiaoxin; et al.
Abstract: Antibody-drug conjugates (ADCs) have been successfully applied clinically as target drugs for cancer. In this study, anti-neural cell adhesion molecule also called CD56 antibody-monomethyl auristatin E (MMAE) conjugate named Promiximab-MMAE was prepared by conjugation of microtubule inhibitor MMAE with Promiximab. The average drug-to-antibody ratio (DAR) of Promiximab-MMAE was 3.13 as analysed by liquid chromatography–mass spectrometry/ mass spectrometry (LC-MS/MS). The targeting capacity and affinity kinetics of Promiximab-MMAE were similar to that of Promiximab after being conjugated with MMAE as tested by flow cytometry and biolayer interferometry analysis. Promiximab-MMAE showed effective anti-proliferation on CD56-positive cell lines (NCI-H524, NCI-H526, and NCI-H69), with the half maximal inhibitory concentration (IC50) values of 19.24, 5.23, and 0.32 nmol/L in vitro, respectively. Promiximab-MMAE of 10 mg/kg every three days with a total of three times was administered in vivo . Results showed that the tumour regression was not recrudesced in NCI-H69 and NCI-H526 xenograft mice models till 52 and 56 days. Moreover, body weight and histopathology of the major organs (liver, spleen, heart, lung, and kidney) showed no significant changes after treatment with Promiximab-MMAE. In conclusion, Promiximab-MMAE is a potential candidate for the treatment of CD56 positive small cell lung cancer.